Aplikasi Managemen Surat Berbasis WEB pada SMK Negeri 1 Boyolali - Indri Ikasari; Donna Setiawati; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2020)
The study entitled Building a web-based mail management application at SMK Negeri 1 Boyolali has the aim to develop a mail management information system in accordance with the administrative requirements of the archives section, simplifying the process of finding incoming and outgoing documents, structuring better mail archives. The research method used to solve various problems that occur is first to collect data. Data collected through observation, interviews and literature study. The next stage is the development of systems that use the waterfall method. This method consists of the stages of system planning (system engineering), needs analysis, design, program writing, testing and system maintenance. The result of his research is that the application is able to shorten the time in the process of managing incoming and outgoing mail, making it easier for users to manage agenda papers, making dispositions, and searching the archive of letters easier and faster.